My many colored days - Seuss, Dr. (New York: Afred A. Knopf, 1996)
The words and illustrations of Dr. Seuss have alway seemed inseparable--a peerless fusion of verbal and visual wit. Yet when the good doctor wrote the manuscript for My Many Colored Days in 1973, he specified that the book should be illustrated by "a great color artist who will not be dominated by me." Twenty-three years later, he has gotten his wish. Steve Johnson and Lou Fancher have produced a series of rich, painterly images that could never be mistaken for faux-Seuss. They have, however, caught something of his simplicity, and just as important, his sense of whimsy.